Host mobility protocol for secure group communication in wireless mobile environments - Kiah, M.L.M.; Martin, K.M. (2008)
Secure group communication allows a set of nodes (or devices) to communicate securely amongst each other over unprotected and open networks. Provision of security for group communication is based on cryptographic services, which relies on careful management of cryptographic keying material. Securing group communication in wired networks is fairly well understood, however wireless networks introduce further challenges as group members may move from one place to another while still remaining in a group session. In this paper we propose a host mobility protocol to govern group member movement in wireless mobile environments. We introduce the use of lists as part of our protocol design in order to facilitate host mobility